Maternal Zinc Level As The Predictor of Neonates Anthropometric - Grecia Ingrid Gultom; Reni Indriyani (Medula, 2020)
Anthropometric measurements are measurements of human body and can be performed on all ages, including neonates. Anthropometry in the neonate consists of body weight, body length, and head circumference. Anthropometry in neonates is essential for assessing intrauterine growth. Zinc is needed by the mother especially in the third trimester. Zinc functions are important in biological aspects such as in protein synthesis, cell division, and nucleic acid metabolism. During embryogenesis, zinc regulates the structure and chromatin function, and gene expression. Zinc deficiency during pregnancy can cause growth retardation by affecting the immune system. Some studies say zinc level does not correlate with birth weight and head circumference while other studies suggest that zinc level is associated with gestation age, weight, body length, head circumference. Cohort studies in China in 2014 says that defisiciency of maternal zinc in early gestation corelate with preterm birth and deficiency in late gestation corelate with Low Birth Weight (LBW).